JEJAKARSITEKTUR DAN LOKALITAS KOTA MASA HIND lA BELAND A DALAMIKONOG~SGAMBARTEMPEL - Baskoro Suyo Banindro (DeKaVe, 2013)
The building architecture has at least some jUnctions, as well as the work of an architect form offruit, trail markers era, technology, as well as the locality of the city landmarks. In its representation issometimes manifested in the work of architectural photography, drawing, emblem of the region in theform of stickers and charming as a form of memento or souvenir.Through an iconographic studies, traces the architecture of a building can be traced how thephysical form, the elements that make up, philosophy, history and even the quot "spirit"; of the architectof the members live in buildings that formed and established.Keywords: Traces of Architecture, Image Paste, Local Identities City.